Genetic Profile of Epidermolysis Bullosa Cases in King Abdulaziz Medical City, Riyadh, Saudi Arabia - Alharthi, Raghad; Alnahdi, Muhannad A.; Alharthi, Ahad; Almutairi, Seba; Al-Khenaizan, Sultan; AlBalwi, Mohammed A. (Frontiers in Genetics, 2022)
Epidermolysis bullosa (EB) is a rare heterogeneous genetic mechanobullous skin disorder that is characterized by an increased skin fragility leading to blistering following minor trauma. EB may be inherited as an autosomal dominant or an autosomal recessive and can be classified into dystrophic EB (DEB), junctional EB (JEB), and EB simplex (EBS). A total of 28 Saudi patients with EB were included in this observational, retrospective chart-review study. Consecutive non-probability sampling technique was used to approach all affected patients. Molecular analysis was done to test the patients’ genomic DNA using a custom design AmpliSeq panel of suspected genes. All disease-causing variants were checked against available public databases. Twelve patients (42.9%) were found to have DEB, 6 patients (21.4%) with JEB, and 10 patients (35.7%) with EBS. The molecular genetic results revealed detections of 24 various homozygous genetic variations in the genes associated with EB and of which, 14 were novel mutations. Most frequent variations were detected in COL7A1 in 12 cases (42.9%) followed by LAMB3 in 5 cases (17.9%), TGM5 in 4 cases (14.3%) and other genes. Furthermore, majority (87.5%) of EB cases was confirmed to have homozygous mutations, and few were documented with positive consanguinity history. Only 3 cases (12.5%) were found to be autosomal dominant displaying heterozygous mutations. This is the first study to establish the EB genetic profile in Saudi Arabia where DEB is the most frequent type. 14 novel mutations were identified which were not previously reported. Consanguineous marriage is clearly recognized in the Saudi population; therefore, we propose a nationwide EB program that would help to extend the spectrum of the genetic profile and to help in the diagnosis and better understanding of this disease.